THE ANALYSIS OF MATHEMATICAL PROBLEMS USING NEWMAN STAGES REVIEWED FROM EMOTIONAL INTELLIGENCE - Yuli Nur Wahidah; Siti Inganah; Agung Deddiliawan Ismail (MEJ (Mathematics Education Journal), 2017)
This study aims to describe student’s mathematical problemsolving abilities with high, medium, and low emotional intelligence. Thetype of this research is descriptive with qualitative-quantitative approach.Subjects in this study were students of Class VII of SMPN 3 Maron whichamounted to 9 students. Data Obtained through questionnaires, tests, andinterviews. Data analysis techniques used are Likert scale, average andpercentage. The results showed the ability to solve mathematical problemsbased on the stages of Newman items, namely: students with high levels ofemotional intelligence: (1) reading the problem, determining keywords, (2)understanding the problem, determining sufficient conditions, necessaryterms and change the problem into the mathematical sentence, (3) theproblem of transformation, determining relevant strategy, (4) process skills,executing strategy, (5) writing the answer, finding the answer and conclusion.Students with moderate emotional intelligence: (1) reading the problem,hesitating to determine keywords, (2) understanding the problem, beingable to determine sufficient conditions and necessary conditions but cannotchange the problem into mathematical sentences, (3) the problem oftransformation, relevant strategies, (4) process skills, being able to executethe strategy but less accurate on the calculation process, (5) writing answers,answers and conclusions are less precise. Students with low emotionalintelligence: (1) reading problems, not being able to determine keywords, (2)understanding the problem, being able to determine sufficient terms andconditions necessary but not yet able to change the problem intomathematical sentences, (3) transformation problem, less relevant, (4)process skills, many errors in the calculation process and did not completeuntil the final stage, (5) writing answers, have not found answers andconclusions.